Hubungan Pelatihan Terhadap Faktor – Faktor Yang Mempengaruhi Produktivitas Kerja Karyawan - Islami, M Iqbal; Setiawardani, Maya (POLITEKNIK NEGERI BANDUNG, 2015)
This research is motivated by the fact that human resources, in this case, the employee is always the active and dominant role in any organization because of human activity as the planner, perpetrator as well as the determinants of the realization of organizational goals. As the development of science and knowledge of the more advanced then the company is expected to make its employees more skilled and trained in their job. One effort that can be done by the company to improve employee productivity of the company is to conduct employee training. This research was conducted at the Commercial Explosives Section PT Pindad (Persero). The purpose of this study was to determine the relationship of employee training and employee productivity factors at the Commercial Explosives Section PT Pindad (Persero) as well as whether the employee training has a significant and positive relationship between labor productivity factors. The assessment study was conducted using survey method, which takes a sample from a population with a questionnaire as the principal means of data collection. The questionnaire consisted of 22 statements. Data analysis methods used are validity, reliability, determination coefficient and hypothesis testing. The results showed that the presence of a significant and positive relationship between the variables of employee training on employee productivity in the Commercial Explosives Section PT Pindad (Persero). The relationship between employee training with labor productivity obtained a value of 71.5%, this value is included in a strong correlation. Then the coefficient of determination (R2) of 51.2% and the adjusted R-square of 50.8% with test t count> t table with significant <0.05, then Ho is rejected and Ha decision is received. Based on the results of testing the hypothesis that there is a significant and positive relationship between employee training on employee productivity.